Potential of natural pasture and locally available supplements in ruminant nutrition in semi-arid location in West Africa - Becker, K.; Gall, C.; Traoré, M.; Sangare, M.; Bartholomew, P.W. (Hohenheim University, 1990)
Discusses the potential of natural pasture and locally available supplements in ruminant nutrition in a semi-arid location in west Africa. Presents data on protein and energy concentration of pasture, on crude nutrients and on energy content of supplement, on nutritive contents of pastures in dry season, and on average body composition of two experimental cattle groups in 1989. Recovery rates and reproducibility of experiments were tested under varying conditions to evaluate polyamide granula as an external marker. Various adaptation periods and possible sources of error in recovering markers were tested. In addition, 2 different methods for obtaining samples were tested under controlled and field conditions.